2017
DOI: 10.1371/journal.pone.0186247
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle mitochondrial bioenergetics and associations with myostatin genotypes in the Thoroughbred horse

Abstract: Variation in the myostatin (MSTN) gene has been reported to be associated with race distance, body composition and skeletal muscle fibre composition in the horse. The aim of the present study was to test the hypothesis that MSTN variation influences mitochondrial phenotypes in equine skeletal muscle. Mitochondrial abundance and skeletal muscle fibre types were measured in whole muscle biopsies from the gluteus medius of n = 82 untrained (21 ± 3 months) Thoroughbred horses. Skeletal muscle fibre type proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 89 publications
10
38
0
Order By: Relevance
“…Thus, very the low polymorphic feature of the horse PRNP gene is worth noting. Furthermore, since previous studies indicated that Thoroughbred, which considered very inbred status, has several SNPs in the other gene, thus we presumed that very low polymorphic PRNP gene is not caused by inbred status of Thoroughbred [34,35]. However, study just in inbred species may skew data and limit interpretation.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, very the low polymorphic feature of the horse PRNP gene is worth noting. Furthermore, since previous studies indicated that Thoroughbred, which considered very inbred status, has several SNPs in the other gene, thus we presumed that very low polymorphic PRNP gene is not caused by inbred status of Thoroughbred [34,35]. However, study just in inbred species may skew data and limit interpretation.…”
Section: Discussionmentioning
confidence: 93%
“…The observation of high LD in this region, and the extremely long haplotypes, indicates that multiple genetic markers may be indicative of the presence of the SINE. [28,31] resulting in muscle fibre type variation [29,32], precocity [4] and rates of differential growth [5,33] in Thoroughbreds, which consequently influences measured speed variables [8] and distance aptitude at various stages of racing. We have shown here, in agreement with previous work discussed above, that although genomic variation at the MSTN locus is the main determinant of best race distance, there are other genetic markers that also contribute to the trait.…”
Section: Discussionmentioning
confidence: 99%
“…Human patients with COQ8A mutations suffered seizures and other neurological symptoms and showed reduced coenzyme Q within skeletal muscle (Jacobsen et al; Mollet et al, 2008). An eQTL for COQ8A in skeletal muscle has already been identified in horses, with a 227 bp SINE insertion in the promotor region of MSTN (g.66495326_66495327ins227) on ECA18 associated with increased expression of COQ8A (previously known as ADCK3 ) in Thoroughbreds (Rooney et al, 2017). However it should be noted that this increase in COQ8A expression did not appear to accompany an COQ8A protein abundance, with no difference in COQ8A protein abundance across genotypes (Rooney et al, 2017).…”
Section: Discussionmentioning
confidence: 99%